(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article analyses problematic issues regarding the importance of using computer technologies in detecting plagiarism in scientific works. It was determined that the problem of plagiarism in science is not only a matter of legislation, but a manifestation of disdain for scientific ethics and moral standards by the scientists themselves. The issue of academic plagiarism must be solved comprehensively and with joint efforts, by applying effective mechanisms to prevent plagiarism. There is no single, complete, comprehensive and generally accepted definition of the category of plagiarism. The essence of plagiarism is the assignment of authorship to someone else’s original (literary, artistic, scientific) work or its part. The development of information technologies creates conditions for detecting illegal borrowing. Special computer programmes and online services check works for originality much faster. The essence and nature of computer technologies, their importance in detecting plagiarism in scientific works are studied. Positive and negative points in the application of computer anti-plagiarism technologies were identified, and an appropriate assessment was given to them. It is substantiated that plagiarism has a certain personification and specificity in various spheres and branches of human activity. The anti-plagiarism system almost does not take into account official parts of scientific works (cover letter, introduction, references to normative legal acts, conclusions, list of used sources) and evaluates them as plagiarism. The algorithm of the anti-plagiarism service must take into account constant stylistic turns and peculiarities of certain branches of science and technology. We believe that the results of new interpretations of scientific work should not be completely new. It is noted that checking with online services does not always reveal translations of texts or borrowings from editions not published online. Accordingly, the results of information processing with the help of specialized anti-plagiarism programmes and services cannot independently be circumstances that allow making reasonable conclusions about the presence or absence of plagiarism in a scientific work. Anti-plagiarism services and programs really help in detecting plagiarism as an additional tool for searching for possible matches of the text, followed by their analysis and processing by a specialist. But the situation with plagiarism still requires the use of plagiarism checking services (even with all their shortcomings). However, no matter how attractive and easy-to-use anti-plagiarism services are, it is necessary to do some work to improve information culture and respect for the copyrights of others.